ANALYSES OF WASTE PRODUCTS OBTAINED BY LASER CUTTING OF AW-3103 ALUMINIUM ALLOY - Jan Loskot; Maciej Zubko; Zbigniew Janikowski (Acta Polytechnica, 2020)
In the presented research, the methods of scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction and transmission electron microscopy were applied to analyse the powder waste obtained by cutting of AW-3103 aluminium alloy using a fibre laser. The scanning electron microscopy allows to analyse the morphology of the waste microparticles, the energy-dispersive X-ray spectroscopy revealed their chemical composition, which was compared with the composition of the original cut material. In the waste powder, mainly plate-like particles were observed that contain almost pure aluminium. X-ray powder diffraction measurements confirmed that the waste powder is composed of aluminium phase with only a slight presence of other phases (magnetite, austenite and graphite) and the transmission electron microscopy revealed the presence of nanoscale particles in this waste powder. Furthermore, it was found that the average size of the microparticles depends on the thickness of the cut material: particles obtained from a thicker workpiece were substantially bigger than those obtained from the thinner material. On the contrary, the dimensions of the workpiece have only a little impact on the particles’ shape and no significant influence on their chemical composition. The results also suggest that the microparticles could be used as an input material for powder metallurgy. But there is also a certain health risk connected with inhalation of such tiny particles, especially the nanoparticles, which can penetrate deep into the human pulmonary system.